Analisis debit banjir metode rasional dan metode HSS Nakayasu terhadap debit banjir terukur Sub DAS Batang Tabir - Nurfaijah; Eri Stiyanto; Wiliya; Ovrianti Nurhadi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
High rainfall and changes in land cover occurring in the Batang Tabir sub-watershed have an impact on surface runoff and increased river flow, triggering flooding and causing road access to be submerged and damage to infrastructure around the river. Therefore, it is necessary to review the flood flow design calculations in the Batang Tabir Sub-Watershed to assess the potential magnitude of flood flows and establish the parameters required for water infrastructure planning. The methods commonly used for flood flow calculations are the Rational Method and the Nakayasu HSS Method. These methods are preferred due to their simplicity, as they only require river data and rainfall data. The selection of an appropriate method for calculating flood discharge must be validated with measured river discharge data. This study aims to determine the design flood discharge method that can be applied to the Batang Tabir Sub-Watershed. This study was conducted by comparing the flood discharge of the Rational and HSS Nakayasu methods with measured flood discharge using frequency distribution based on relevant statistical parameters. The results of the flood discharge calculations using the Rational method for a return period of 2–100 years are closer to the measured flood discharge, with the Rational method yielding a flood discharge of 494.05–1,385. 48 m³/s, the flood discharge using the Nakayasu HSS method for a return period of 2–100 years was 769.32–2,157.41 m³/s, and the measured flood discharge for a return period of 2–100 years was 375.22–1,337.44 m³/s. The validation and evaluation results show that the smallest error value (VE) is found in the Rational method, which is 9%, with the Nash Sutcliffe Efficiency (NSE) value falling into the very good category at 94%. Meanwhile, the Nakayasu HSS method yields the largest error value (VE) at 69%, and the NSE value falls into the unsatisfactory category at 17%. Therefore, the Rational method has a better level of suitability and can be used as a reference in infrastructure planning in the Batang Tabir Sub-Watershed.